Batasan Kadar Dua Kulah sebagai Standar Kesucian Air Menurut Imam Syafii dan Ibnu Taimiyah - Sepmin Alfurqan; Rustam Efendi; Ridwan Ridwan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to find out how Imam Shafii and Ibn Taimiyah view the limit of two kulahs as a standard for the purity of water, as well as how the comparative analysis and argumentative basis for the opinions of Ibn Taimiyah and Imam Syafii regarding the limit of two kulahs as a standard for the purity of water. This research uses descriptive qualitative research (non-statistical) using the library research method (literature review) which is supported by normative and comparative approaches. The results of this study indicate that there are different views between Imam Shafii and Ibn Taimiyah regarding the matter of limiting the levels of two kulahs as a standard for the purity of water. Ibn Taimiyah did not make the level of two kulahs a standard for the purity of water, but rather changes in the properties of the water (color, taste or smell). Meanwhile, Imam Syafii made two kulahs as a standard for the purity of water if the water is unclean, provided that the properties of the water do not change. The arguments used by the two scholars are all valid, but the cause of differences of opinion is the interpretation and understanding of these arguments. The implications of this research are expected to be a reference for the world of academics and Muslims in general, especially on the issues of taharah and the sanctity of water.